Recent advances in superhydrophobic surfaces and their relevance to biology and medicine. (4th February 2016) - Ciasca, G; Papi, M; Businaro, L; Campi, G; Ortolani, M; Palmieri, V; Cedola, A; De Ninno, A; Gerardino, A; Maulucci, G; De Spirito, M
Abstract: By mimicking naturally occurring superhydrophobic surfaces, scientists can now realize artificial surfaces on which droplets of a few microliters of water are forced to assume an almost spherical shape and an extremely high contact angle. In recent decades, these surfaces have attracted much attention due to their technological applications for anti-wetting and self-cleaning materials. Very recently, researchers have shifted their interest to investigate whether superhydrophobic surfaces can be exploited to study biological systems. This research effort has stimulated the design and realization of new devices that allow us to actively organize, visualize and manipulate matter at both the microscale and nanoscale levels. Such precise control opens up wide applications in biomedicine, as it allows us to directly manipulate objects at the typical length scale of cells and macromolecules. This progress report focuses on recent biological and medical applications of superhydrophobicity. Particular regard is paid to those applications that involve the detection, manipulation and study of extremely small quantities of molecules, and to those that allow high throughput cell and biomaterial screening.